Harnessing CRISPR-Cas for Targeted Epigenetic Manipulations: a physiological study of Gene Regulation - Qammar Shaker Hmood (Journal of Medical Genetics and Clinical Biology, 2024)
Genome engineering, epigenome editing, as one of the prominent research techniques, has also become instrumental in discovering the gene expression regulation mechanisms and exploring their physiological correlates in health and pathology. This review summarizes the state-of-the-art CRISPR-Cas strategies that focus on epigenetics modification and projects its utility in molecular physiology of gene regulation. In this course we will delve into how CRISPR-Cas systems interact with epigenetic signals through DNA methylation, histone modifications and accessibility to chromatin. Then we look at the physiological effects of epigenetic modulations in cellular differentiation and development, cellular signal and homeostasis, disease pathogenesis, and therapeutic for application. Issues and perspectives on how epigenome manipulations can revolutionize therapeutics are also emphasized exploring the potential of precision medicine and individualized therapies. Overall, the review stresses the pivotal role of epigenetic modulation in the development of our understanding of gene expressions/mediation and cellular physiology. It also provides some inputs on the potential directions that the field of genetic engineering might take in the future.